Immobilization of alpha- amylase on aminated polyimide membrane: Preparation, characterization, and properties - ÇAKMAKÇI, EMRAH; KAHRAMAN, MEMET VEZİR; DANIŞ, ÖZKAN; DEMİR, SERAP (WILEY-V C H VERLAG GMBH, 2014)
-amylase was covalently immobilized on functionalized polyimide (PI) membranes via glutaraldehyde (GA) activation. 3,3,4,4-Benzophenonetetracarboxylic acid dianhydride (BTDA) and 4,4-oxydianline (4,4-ODA) based polyimide membranes were obtained via thermal imidization. Free amine groups on the surface of the polyimide membranes were generated by the amination reaction of polyimides with hexamethylenediamine (HMDA). Surface-aminated membranes were subjected to enzyme immobilization after GA activation. Immobilization efficiency and enzyme activity of -amylase was examined at various pH (3.0-8.0) and temperature (15-80 degrees C). The storage stability and reusability of immobilized -amylase were investigated. Immobilization yield was found as 359.53mg per gram of modified polyimide films. Enzyme assays demonstrated that the immobilized enzyme exhibited better thermo stability than the free one. The storage stability and reusability improved by the immobilization on this enzyme support. Free enzyme lost its activity completely within 15 days. On the other hand, the immobilized enzyme retained 79.98% of its activity after 30 days. These results confirmed that -amylase was successfully immobilized and gained more stable character compared to the free enzyme.
Keywords: Alpha amylase; BTDA-ODA; Enzyme immobilization; Polyimide; Surface amination; STARCH-CONVERTING ENZYMES; COVALENT IMMOBILIZATION; MICROSPHERES; PERFORMANCE; SURFACE; BEADS